Improving Communication English Speaking Skill through Listening Practice for Non-English Majored Students - Ary Iswanto Wibowo; Sayyid Khairunas (LPPM Universitas Bina Sarana Informatika, 2019)
The purpose of this study is to investigate the improvement of the student’s achievement in speaking by listening practice for Broadcasting and Public Speaking class at Bina Sarana Informatika University. These classes got English subject at even semester. They learnt to focusing on speaking, that’s why the researchers help the students to achieve their performance in speaking skill. By using listening practice through audio and video, the researchers hope that they will improve their speaking. The method that has been used by this research was Classroom Action Research (CAR) where the researchers as well as the teachers involved in the class that they are observing. Data were taken by sample of 20 students from each class. Technique for collecting data was descriptive qualitative and quantitative. Technique for analyzing data was used descriptive which describe the finding of the research which used some tables, frequency which was benefit to describe the achievements of the students in speaking from pre-test, cycle 1, and cycle 2. The finding of the research was the students’ achievement in speaking were good by using listening practice during a semester. The final achievement from Broadcasting got score 6,24 in average and Public Relation class got score 7,06.